2020
DOI: 10.3390/met10030410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat Treatment Condition on Microstructural and Mechanical Anisotropies of Selective Laser Melted Maraging 18Ni-300 Steel

Abstract: 18Ni-300 maraging steel produced by the selective laser melting (SLM) process has a unique microstructure that is different from that of the same alloy processed by conventional methods. In this paper, maraging steels were fabricated by the selective laser melting process and their microstructures and mechanical properties were investigated in terms of post heat treatment conditions. Moreover, the effect of different heat treatments on the mechanical anisotropy was studied in detail. The micro Vickers hardness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 18 publications
6
42
0
Order By: Relevance
“…The maraging steel produced by the LPBF presented a hardness of ~340–350 Hv in as-built state and 570–590 Hv (i.e., ~1.7 times higher than in the as-built) after HT850 heat treatment. These results can be easily explained by the precipitation strengthening mechanism, i.e., a uniform distribution of fine Ni-rich intermetallic precipitates during the aging of a ductile, low-carbon martensite structure [ 12 , 17 , 22 , 23 , 24 ]. The hardness variations among the three directions are small and within statistical deviations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The maraging steel produced by the LPBF presented a hardness of ~340–350 Hv in as-built state and 570–590 Hv (i.e., ~1.7 times higher than in the as-built) after HT850 heat treatment. These results can be easily explained by the precipitation strengthening mechanism, i.e., a uniform distribution of fine Ni-rich intermetallic precipitates during the aging of a ductile, low-carbon martensite structure [ 12 , 17 , 22 , 23 , 24 ]. The hardness variations among the three directions are small and within statistical deviations.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the beads generated during the LPBF process are observed in the wear plane of each specimen (white line). Further details regarding the microstructure, and tensile behavior of the LPBF-processed maraging steels used in this study can be also found in [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations